Strengthening Global Cybersecurity: India’s Engagement in International Cybercrime Control - Pratap, Ajay (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
In an increasingly interconnected digital world, cybercrime has emerged as a transnational threat demanding coordinated global responses. India, as one of the largest digital economies, plays a pivotal role in fostering international cooperation to combat cybercrime. This study explores India’s engagement in global cybersecurity initiatives, focusing on its bilateral and multilateral collaborations, legislative frameworks, and partnerships with international organizations such as INTERPOL, UNODC, and the Global Forum on Cyber Expertise. The paper highlights India's efforts to harmonize cyber laws, participate in information-sharing networks, and contribute to cross-border investigations. It also addresses the challenges India faces, including jurisdictional issues, data sovereignty concerns, and evolving cyber threats. By analyzing India’s proactive strategies and policy reforms, the study underscores the nation's commitment to enhancing global cybersecurity and shaping a cooperative, resilient digital ecosystem.